KOMPENSASI EKSEKUTIF DAN MANAJEMEN LABA: BUKTI EMPIRIS DARI NEGARA-NEGARA TELUK - Eko Suyono (Fakultas Ekonomi Universitas Pekalongan, 2017)
This study intends to examine the effect of executive compensation on earnings management for firms listed on the Gulf Stock Exchange, i.e., Saudi Arabia, Qatar, United Arab Emirate, Kuwait, Oman, and Bahrain. Using a purposive approach in the sampling technique, this study ended-up with 17 companies as samples for 2011-2015 periods. In other words, this study succeeded in getting 85 observations. The data collected were analyzed by simple linear regression and the results show that executive compensation has no significant effect on earnings management practices on firms listed on the Gulf Stock Exchange. The finding shows that the magnitude of the value of executive compensation is not a consideration for managers in the practice of earnings management as a form of managers’ opportunistic behavior. Although this study uses relatively small sample size, the results of this study contribute to providing empirical evidence of the relationship between executive compensation and earnings management in developing countries. Keywords: executive compensation, earnings management, managers’ opportunistic behavior